Positively charged residues at the channel mouth boost single-file water flow. (4th July 2018) - Horner, Andreas; Siligan, Christine; Cornean, Alex; Pohl, Peter
Abstract : Positively charged residues in the vicinity of the channel entrance or exit accelerate single-file water flow. Abstract : Water molecules lose two of their four bulk neighbours when entering single-file channels. This process may be sensitive to the presence of positive and negative charges at the channel mouth, since the costs for dehydrating cations and anions differ by a large margin. However, it is not known whether entrance charges affect the single channel water permeability ( p f ). So far, p f is only known to be governed by H-bond formation between permeating water molecules and wall-lining residues. Here we compare the p f values of five different aquaporin species (AQP1, AQPZ, AQP4 wild type, and two phosphorylation mimicking AQP4 mutants) that offer the same number of hydrogen bond donating and receiving residues in their single-file region but display different entrance charges. The p f measurements were performed with reconstituted lipid vesicles. We assessed (i) the osmotically induced vesicle deflation from the light scattering intensity in a stopped-flow device and (ii) the aquaporin abundance by fluorescence correlation spectroscopy. Substitution of serine at positions 111 and 180 in AQP4 for aspartic acid showed only a marginal effect on p f, suggesting that negative entrance charges are of minor importance. In contrast, the total number of positively charged amino acid side chains at entrances and exits correlates with p f : a total of three, four and seven charges of AQP4, AQPZ, and AQP1 translate into p f values of 1.1, 1.8, and 3.2 × 10 −13 cm 3 s −1, respectively. Thus, positive interfacial charges boost the p f value of AQP1 to three times the value of AQP4. Nevertheless, the number of hydrogen bond donating and receiving residues in the single-file region remains the major determinant of p f . Their effect on p f may be a hundredfold larger than that of interfacial charges.